Taxonomic revision of the genus Cabassous McMurtrie, 1831 (Cingulata: Chlamyphoridae), with revalidation of Cabassous squamicaudis (Lund, 1845) - Feijó, Anderson; Anacleto, Teresa Cristina (Zootaxa, 2021)
Cabassous comprises armadillos lacking a full osteoderm cover in the tail, justifying its common name naked-tailed armadillos. In the only taxonomic revision of the genus, in 1980, four living species were recognized, including a polytypic taxon with two subspecies. Recent studies have questioned this classification, but a comprehensive taxonomic review is lacking. Here, we revise the taxonomy of the genus Cabassous using complementary morphological approaches and clarify the geographical limits of naked-tailed armadillo species. Based on qualitative and quantitative analyses, we recognize five living species: C. centralis, C. chacoensis, C. squamicaudis, C. unicinctus, and C. tatouay. Most of the species can be easily differentiated using external or cranial traits, except C. centralis and C. unicinctus, which share several morphological features. The scutes pattern on the cephalic shield is an important diagnostic feature in naked-tailed armadillos and can be easily applied in field studies. Cabassous squamicaudis and C. unicinctus were previously treated as subspecies but we show they have conspicuous diagnostic traits, without mixture of characters even in closer contact. Cabassous species can be classified as open-dwellers (C. chacoensis and C. squamicaudis), forest-dwellers (C. centralis and C. unicinctus), or of more generalist habits (C. tatouay). We designate a lectotype for C. unicinctus to preserve its long-term nomenclature use.